Perception and Experience of Youth About Youths Sexual and Reproductive Health Services in Western Ethiopia: A Community-Based Cross Sectional Study. (November 2022) - Tilahun, Temesgen; Tesfaye Bekuma, Tariku; Getachew, Motuma; Oljira, Rut; Seme, Assefa
Objectives: The use of youth sexual and reproductive health (YSRH) services is low in poor nations like Ethiopia. This puts individuals at risk for a variety of sexual and reproductive health issues. Thus, the goal of this study is to evaluate how young people in East Wollega, Western Ethiopia, perceive and use YSRH services. Methods: A community-based cross-sectional quantitative study mixed with a qualitative inquiry was conducted among 771 participants from February 1 to 28, 2020. Data were collected through face-to-face interviews using pretested structured questionnaires adopted from reviewed works of literature on YSRH services. Data were entered using Epi Info version 7.0 and analyzed by SPSS version 20. The qualitative data was collected using interview guides and checklists. These data were analyzed using a thematic framework approach. Results: In this study, 48.2% of teens felt that the YSRH service units' location within the medical facilities was inconvenient and difficult to access. More than half, 71.3% of participants, concurred that the health providers offer services that are technically sound. The confidentiality of information is disputed by 18% of participants at YSRH service locations. The limited awareness and use of YSRH services was investigated. Because of their fear of embarrassment, lack of privacy, the providers' attitudes and workload, and the service unit's awkward location, the adolescents believe they lack the confidence to use YSRH services. Conclusion: Due to low awareness, providers' attitudes, and characteristics specific to health facilities, such as poorly placed service sites inside such facilities, a lack of services offered there, and a terrible work environment, youth had a negative opinion of YSRH services. Therefore, it is advised that families, local authorities, the medical field, the educational field, and the media all collaborate to alter public opinions of juveniles by utilizing youth-friendly strategies. The authors advise health facilities to respect young people's privacy, alter health workers' attitudes, let them use the services, remove obstacles to payment, designate enough health workers for both working and non-working hours, and reorganize the services.